Jane Austen and the Oxford English Dictionary - Brewer, C (2010)
During the period in which the first edition of the OED was compiled, from the 1860s to 1928, it was unexceptionable to turn to great writers as a source of information on the history and development of the English language. In the words of W. D. Whitney, the distinguished Sanskritist and editor of the influential Century Dictionary (an early rival to OED), 'A great body of literary works of acknowledged merit and authority, in the midst of a people proud and fond of it, is an agent in the preservation and transmission of any tongue, the importance of which cannot be easily over-estimated'. Consequently it is not surprising that the OED, a dictionary based on its quotations, sought and found them, in vast numbers, in the works of Shakespeare (c. 33,000 quotations), Walter Scott (c. 15,000), Chaucer (c. 11,000), Dickens (c. 8,200), Tennyson (c. 6,700), and other writers highly valued by the Victorians and Edwardians. All these writers are male, reflecting then-standard views about the literary canon and the importance of men, rather than women, as creators of language and culture. Unusually for a female author, Austen's works are quoted many times in the OED. Unusually for any author, her works received special attention not only in the first edition of the dictionary (c. 700 quotations), but also - despite their date of composition, which would, one might have though, have made them ineligible for quotation - in the twentieth-century Supplement to the OED edited by R. W. Burchfield (c. 350 quotations). Austen's letters and novels are also quoted generously in the early stages of OED3. Particularly in the first two editions, many of these quotations are for domestic and household vocabulary and are also examples of first cited use in the dictionary. This paper explores the question whether the OED tells us about Jane Austen's use of language, or whether the OED's use of Jane Austen tells us about the assumptions and methods of the lexicographers.